Impact of HIV-1 infection and pregnancy on maternal health: comparison between perinatally and behaviorally infected young women - Munjal I; Dobroszycki J; Fakioglu E; Rosenberg MG; Wiznia AA; Katz M; Steiner A; Sansary J; Heo M; Abadi J (Dove Medical Press, 2013)
Iona Munjal,1 Joanna Dobroszycki,2 Esra Fakioglu,1 Michael G Rosenberg,2 Andrew A Wiznia,2 Mindy Katz,3 Aileen Steiner,3 Jorge Sansary,2 Moonseong Heo,4 Jacobo Abadi21Department of Pediatrics, Montefiore Medical Center, 2Department of Pediatrics, 3Department of Medicine, Jacobi Medical Center, 4Department of Epidemiology and Population Health, Albert Einstein College of Medicine, Bronx, NY, USABackground: The introduction of combination antiretroviral therapy has resulted in improved survival and quality of life for individuals infected with the human immunodeficiency virus (HIV). There is, as expected, a growing population of perinatally HIV-infected women who are, have been, or will become pregnant. We describe a large cohort of perinatally infected women, compare it with a similar age-matched behaviorally HIV-infected group, and examine factors affecting maternal and infant health.Methods: We reviewed the records of 30 perinatally infected women who gave birth at two hospitals between January 2000 and December 2011. The comparison group comprised behaviorally infected women who delivered at these hospitals during the same period. The outcome measures were differences in CD4 counts and viral load between the cohorts, and comparisons of maternal morbidity, mortality, and mother-to-child HIV transmission.Results: Median CD4 counts were significantly lower in the perinatal group before, during, and after pregnancy. The median viral load was significantly higher in the perinatal group. Interval prepregnancy to post partum viral load decline was also greater in the behavioral group. Viral load decreases in the perinatal population were not sustained in the post partum period, at which time viral load trended back to prepregnancy levels. There was one mother-to-child HIV transmission in a perinatally infected woman. Over an extended 4 years of follow-up, there were four deaths in the perinatal group and none in the behavioral group.Conclusion: After delivery, the differences between perinatally and behaviorally infected mothers accentuate, with immunologic deterioration in the former group. The perinatal population may require novel management strategies to ensure outcomes comparable with those observed in the behavioral group.Keywords: human immunodeficiency virus infection, pregnancy, maternal health, perinatal infection, behavioral infection